SOCIETY COMMUNICATION PATTERNS IN THE ERA OF INFORMATION TECHNOLOGY CASE STUDY COASTAL VILLAGE, BESUKI DISTRICT, DISTRICT SITUBONDO - POLA KOMUNIKASI MASYARAKAT NELAYAN DI ERA TEKNOLOGI INFORMASI STUDI KASUS DI DESA PESISIR, KECAMATAN BESUKI, KABUPATEN SITUBONDO - Trisnani - (BPSDMP Kominfo Manado, 2016)
This research was conducted in May 2016. Fishermen society still be the first goverment priority because even they live in the coast which far from cities and no transportation, modernity and without communication with outside, but fishermen has promising in earnings salary from life-coast take part in the country's economy. Survey method was chosen by the writer with incidental determining sample method which every people who meet the writer would be chosen as the representatives as long as the representatives are reasonable to give valid information. The traditional communication is still used by the fishermen in this era. The fishermen should meet the people who wants to talk with and doing a face to face communication is the problem in communication side. Fishing communities have not completely utilized information technology because the Information Technology skill and utility have been not applied in this life-coast. Information Technology should be utilized by the fishermen society to keep in touch with others and improving the knowledges and income about sea.Keywords: Patterns, Communication, Fishermen Society, Information TechnologyPenelitian ini, dilakukan pada Mei 2016, masyarakat nelayan masih menjadi prioritas utama karena disamping kehidupannya dipesisir pantai yang jauh dari jangkauan transportasi dan komunikasi namun sebetulnya memiliki penghasilan yang sangat menjajikan dari hasil kelautan ikut andil dalam perekonomian negara. Penelitian menggunakan metode survei dengan teknik penarikan sampel berdasarkan accidental kebetulan, yaitu siapa saja yang bertemu dengan peneliti dapat digunakan sebagai sampel, bila dipandang orang yang kebetulan ditemui cocok sebagai sumber data. Permasalahan bagaimana pola komunikasi masyarakat nelayan di era teknologi informasi, pola komunikasi masyarakat nelayan masih menggunakan komunikasi tradisional berkomunikasi secara langsung bertatap muka (face to face). Masyarakat nelayan belum sepenuhnya memanfaatkan teknologi informasi karena disamping belum memiliki ketrampilan TIK juga belum ada Teknogi informasi yang diterapkan di masyarakat nelayan sebagai sumber informasi yang bisa dimanfaatkan masyarakat nelayanKata Kunci: Pola, Komunikasi, Masyarakat Nelayan ,Tegnologi Informasi